Immature gastric teratoma in an infant: A case report - Vyas, Nandini; Swain, Meenakshi; Jayaram, Harish (Indian Journal of Case Reports, 2020)
Immature gastric teratoma is an extremely rare embryonal neoplasm. Although teratomas have been identified in most body regions, the sacrococcygeal is the most commonly involved site, followed by cervicofacial, mediastinal, gonadal, and retroperitoneal regions. The stomach is rarely involved, accounting for